Microstrip Filters: A Review of Different Filter Designs Used in Ultrawide Band Technology - Bohra, Hussain; Prajapati, Giriraj (UI Scholars Hub, 2020)
In this study, optimization techniques applied in designing microstrip bandpass ultra-wideband (UWB) filters are presented. Optimization based on various defected ground structure techniques, resonator designs, and type of dielectric materials is discussed. Microstrip bandpass filters implemented at UWB frequency bands used in wireless communication systems have key features to control frequency response in passband and stopband. Optimization techniques are studied to attain optimum performance of bandpass microstrip filters to ensure minimum insertion loss, high selectivity, compactness, sharp transitions at cut-off frequencies, high return loss, and excellent linearity. Extensive study shows that proper selection of fabrication techniques and type of material optimizes the performance of microstrip filter design, thereby increasing its practicability for emerging wireless communication systems.